Polymer all-solid-state electrolyte, method for preparing the same, and use thereof

CN123017749APending Publication Date: 2026-10-30DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611495914.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该方法能够提高体系中可迁移钠离子的数量,但若Lewis碱位点与钠离子配位作用过强,容易提高Na+迁移能垒,使迁移阻力增大,导致钠离子迁移能力较低;若配位作用过弱,则难以有效促进钠盐解离

Benefits of technology

本发明提供的聚合物全固态电解质通过包括含有Lewis碱位点和Hammett型强吸电子取代基的功能聚合物,可以使得聚合物全固态电解质兼具强钠盐解离能力和低Na+迁移能垒,从而实现了离子电导率和电极/电解质界面稳定性的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017749A_ABST
    Figure CN123017749A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of all-solid-state polymer electrolyte, and particularly relates to a polymer all-solid-state electrolyte, a preparation method and application thereof, the polymer all-solid-state electrolyte comprises a functional polymer containing Lewis base sites and Hammett type strong electron-withdrawing substituents, a polymer matrix and a sodium salt, wherein the Lewis base sites comprise at least one of sulfonate, carboxylate and phosphate, and the Hammett type strong electron-withdrawing substituents comprise at least one of fluoroalkyl, perfluoroaryl and nitro-substituted aryl. The polymer all-solid-state electrolyte provided by the present application can have strong sodium salt dissociation ability and low Na + migration energy barrier, thereby achieving synergistic improvement of ionic conductivity and electrode / electrolyte interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of all-solid-state polymer electrolyte technology, and in particular to a polymer all-solid-state electrolyte, its preparation method, and its application. Background Technology

[0002] With the rapid development of renewable energy grid connection and artificial intelligence computing, higher demands are being placed on electrochemical energy storage technology. Energy storage systems not only need high energy density to meet long-term power supply needs, but also high power density to respond to rapid load changes, and long cycle life to reduce total lifespan costs. Sodium resources, due to their abundant reserves and low cost, make sodium-based energy storage systems considered an important supplement to lithium-based energy storage systems. Among them, sodium metal capacitors, which combine Faraday and capacitive energy storage mechanisms, theoretically can achieve a synergistic improvement in high energy density, high power density, and long cycle life, and have therefore attracted widespread attention.

[0003] However, the development of sodium metal capacitors remains limited by key issues such as ion transport kinetics, electrode / electrolyte interface stability, and safety. As a crucial component of sodium metal capacitors, commercial liquid electrolytes pose risks of leakage, combustion, and explosion due to their fluidity and volatility. Furthermore, their mechanical strength is insufficient to effectively suppress sodium dendrite growth, easily leading to internal short circuits and thermal runaway within the battery. Therefore, polymer solid electrolytes, due to their superior mechanical strength and interfacial contact properties, are considered an important technological approach to improving the safety and stability of sodium-based energy storage devices.

[0004] Currently, most polymer solid electrolytes have an ionic conductivity of only 10 at room temperature. -6 -10 -7 The current density (S / cm) of sodium metal capacitors is insufficient to meet the rapid ion transport requirements at high current densities, thus limiting their application in fast-charging sodium-based energy storage devices. To improve the ion transport performance of polymer solid electrolytes, existing technologies typically introduce functional polymers containing Lewis base sites into the polymer matrix. These functional polymers utilize their coordination with sodium ions to promote sodium salt dissociation and provide sites for sodium ion transport. This method can increase the number of mobile sodium ions in the system; however, if the coordination between the Lewis base sites and sodium ions is too strong, it can easily increase the sodium content. + A migration barrier increases migration resistance, resulting in lower sodium ion migration ability; if the coordination interaction is too weak, it is difficult to effectively promote sodium salt dissociation. Therefore, the regulation strategy based on a single coordination interaction is still difficult to simultaneously achieve both the strong sodium salt dissociation ability of polymer solid electrolytes and low sodium ion migration ability. + The comprehensive requirements of migration energy barriers.

[0005] Therefore, it is necessary to develop a method that combines strong sodium salt dissociation ability with low Na+ content. +The development of polymer solid electrolytes with migration energy barriers, thereby achieving a synergistic improvement in ionic conductivity and electrode / electrolyte interface stability, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the aforementioned shortcomings in existing technologies, the present invention aims to provide a polymer all-solid-state electrolyte, its preparation method, and its applications. The polymer all-solid-state electrolyte provided by this invention utilizes a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, enabling the polymer all-solid-state electrolyte to possess both strong sodium salt dissociation capability and low sodium content. + The migration barrier is reduced, thereby achieving a synergistic improvement in ionic conductivity and electrode / electrolyte interface stability.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a polymer all-solid electrolyte comprising: a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, a polymer matrix, and a sodium salt, wherein the Lewis base sites include at least one of sulfonate, carboxylate, and phosphate, and the Hammett-type strong electron-withdrawing substituents include at least one of fluoroalkyl, perfluoroaryl, and nitro-substituted aryl.

[0008] Furthermore, the polymer all-solid electrolyte is in the form of a film, and the thickness of the polymer all-solid electrolyte is 20-80 micrometers; And / or, the mass ratio of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents to the polymer matrix is ​​(0.1-10):1; And / or, the mass ratio of the polymer matrix to the sodium salt is 1:(0.2-5). And / or, the fluoroalkyl group includes at least one of polyfluoroalkyl and perfluoroalkyl groups; And / or, the number-average molecular weight of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is 10,000-80,000 g / mol; And / or, the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate polymers, and polysiloxane polymers; And / or, the sodium salt includes at least one of NaFSI and NaTFSI.

[0009] Furthermore, the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is a random copolymer, and the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained by copolymerizing a first functional monomer containing Lewis base sites and a second functional monomer containing Hammett-type strong electron-withdrawing substituents.

[0010] Furthermore, the molar ratio of the first functional monomer containing the Lewis base site to the second functional monomer containing the Hammett-type strong electron-withdrawing substituent is 1:(0.4-10). And / or, the first functional monomer containing the Lewis base site includes at least one of sulfobetaine monomers, carboxybetaine monomers, and phosphorylcholine monomers; And / or, the first functional monomer containing the Lewis base site includes at least one of sulfobetaine methacrylate, carboxybetaine methacrylate, and 2-methacryloyloxyethyl phosphocholine; And / or, the second functional monomer containing a Hammett-type strong electron-withdrawing substituent includes at least one of 2,2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, dodecafluoroheptyl methacrylate, perfluorohexylethyl methacrylate, 4-trifluoromethylstyrene, pentafluorostyrene, and nitrostyrene.

[0011] Furthermore, the raw materials for preparing the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents include the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, a chain transfer agent, an initiator, and an oxygen scavenger; the chain transfer agent includes at least one of 4-cyano-4-(phenylcarbonylthio)pentanoic acid, 2-cyano-2-propyldodecyl trithiocarbonate, cumyl dithiobenzoate, and 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid; the initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and peroxide... The oxygen scavenger comprises at least one of benzoyl persulfate and ammonium persulfate; the oxygen scavenger comprises at least one of sodium dithionite, sodium sulfite, sodium bisulfite, ascorbic acid, glucose, and triethanolamine; the mass ratio of the chain transfer agent to the first functional monomer containing the Lewis base site is (0.005-0.5):1; the mass ratio of the initiator to the chain transfer agent is 1:(1-35); the mass ratio of the oxygen scavenger to the first functional monomer containing the Lewis base site is (0.0003-0.1):1.

[0012] Furthermore, the preparation method of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents includes the following steps: S1. Add the co-solvent to the first organic solvent and stir until it is uniformly dissolved to obtain a first organic solvent system containing the co-solvent; then add the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, the chain transfer agent, the initiator and the oxygen scavenger to the first organic solvent system containing the co-solvent, stir to remove oxygen under an inert atmosphere, and then carry out a polymerization reaction. After the reaction is completed, a reaction solution of a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained. S2. The reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 is added to the precipitant, stirred, and the polymer is precipitated. Then, solid-liquid separation is performed, and the obtained solid is dried to obtain the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents.

[0013] Furthermore, the first organic solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, and tetrahydrofuran; And / or, the co-solvent includes at least one of lithium chloride, lithium bromide, sodium chloride, sodium bromide, potassium chloride, and potassium bromide; And / or, the mass-to-volume ratio of the first functional monomer containing the Lewis base site to the first organic solvent is 1 g: (5-100 mL). And / or, the mass ratio of the cosolvent to the first functional monomer containing the Lewis base site is (0.01-1):1; And / or, in step S1, the stirring temperature is 20-40℃ and the time is 5-20 minutes; And / or, in step S1, the inert atmosphere includes a nitrogen atmosphere or an argon atmosphere; And / or, in step S1, the temperature for stirring and deoxygenation is 20-40℃, and the time is 1-2 hours; And / or, in step S1, the polymerization reaction is carried out at a temperature of 60-80°C for 2-24 hours; And / or, in step S2, the stirring time is 20-60 min; And / or, in step S2, the precipitant is a mixed solvent of alcohol solvent and alkane solvent; the alcohol solvent includes at least one of methanol, ethanol, isopropanol, and n-butanol; the alkane solvent includes at least one of n-hexane, cyclohexane, n-heptane, and petroleum ether; the volume ratio of the alcohol solvent to the alkane solvent is 1:(0.5-2). And / or, in step S2, the drying temperature is 40-80℃ and the time is 12-24h; And / or, in step S2, the volume ratio of the reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 to the precipitant is 1:(5-50); the solid-liquid separation method includes vacuum filtration, filtration or centrifugation.

[0014] In a second aspect, the present invention provides a method for preparing a polymer all-solid-state electrolyte as described in the first aspect, the method comprising the following steps: In an inert gas environment, the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, the polymer matrix, and the sodium salt are mixed, and the resulting mixture is dissolved in a second organic solvent and mixed evenly to obtain a mixed solution B; the mixed solution B is placed in a mold and then dried to obtain the polymer all-solid electrolyte.

[0015] Furthermore, the second organic solvent includes at least one of ethylene glycol dimethyl ether, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, tetrahydrofuran, and 1,3-dioxolane; And / or, the mass-to-volume ratio of the polymer matrix to the second organic solvent is 1 g: (8-30 mL). And / or, the mixing temperature is 40-80℃, and the time is 3-12h; And / or, the mold includes a polytetrafluoroethylene mold; And / or, the drying temperature is 40-80℃, and the time is 12-24 hours.

[0016] Thirdly, the present invention provides an application of a polymer all-solid-state electrolyte as described in the first aspect or a polymer all-solid-state electrolyte prepared by the preparation method described in the second aspect in a sodium-based solid-state energy storage device.

[0017] Compared with the prior art, the beneficial effects of the present invention include at least the following: The polymer all-solid-state electrolyte provided by this invention, through the inclusion of functional polymers containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, enables the polymer all-solid-state electrolyte to possess both strong sodium salt dissociation ability and low Na+ content. +The migration barrier is reduced, thereby achieving a synergistic improvement in ionic conductivity and electrode / electrolyte interface stability. Attached Figure Description

[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0019] Figure 1 Raman spectroscopy results of polymer all-solid-state electrolyte membranes provided in Examples 1, 1, 3, and 4 of this invention; Figure 2 This is a comparison chart of the coulombic efficiencies of Na-Cu half-cells prepared using the polymer all-solid-state electrolyte membranes provided in Example 1, Comparative Example 1, and Comparative Example 2 of this invention. Figure 3 Comparison chart of rate performance of polymer all-solid electrolyte membranes provided in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention; Figure 4 The exchange current density diagrams of the polymer all-solid electrolyte membranes provided in Embodiment 3 and Comparative Examples 1-3 of the present invention are shown. Figure 5 The polymer all-solid-state electrolyte membranes prepared for Examples 3, 1, and 2 of this invention were subjected to a reaction at 2 A·g -1 Long-cycle performance at current density; Figure 6 The hydrogen nuclear magnetic resonance spectrum of copolymer A prepared in Example 1 of this invention; Figure 7 The infrared spectrum of copolymer A prepared in Example 1 of this invention; Figure 8 This is a comparison of the gel permeation chromatography (GPC) curves of copolymer A prepared in Example 1 of the present invention and copolymer A prepared in Comparative Example 5. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. Process parameters in the following embodiments that do not specify specific conditions are generally based on conventional conditions, unless otherwise specified, indicating that all raw materials are commercially available or commonly used in this industry.

[0021] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0022] In a first aspect, the present invention provides a polymer all-solid electrolyte comprising: a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, a polymer matrix, and a sodium salt, wherein the Lewis base sites include at least one of sulfonate, carboxylate, and phosphate, and the Hammett-type strong electron-withdrawing substituents include at least one of fluoroalkyl, perfluoroaryl, and nitro-substituted aryl.

[0023] Specifically, the Lewis base site (electron pair donor) provides coordination sites, which are mainly responsible for promoting sodium dissociation and providing the initial ion transport channel.

[0024] Hammett-type strong electron-withdrawing substituents refer to groups with a Hammett constant (σ) of not less than 0.3 and strong electron-withdrawing ability. These strong electron-withdrawing substituents are highly polar and exhibit weak ion-dipole interactions with sodium ions. If σ is less than 0.3, the ability to regulate sodium ions is very weak and insufficient to facilitate the dissociation of sodium ions.

[0025] Perfluoroaryl group refers to a group formed when all the hydrogen atoms originally attached to the carbon atoms of the aromatic ring in the aryl group are replaced by fluorine.

[0026] In existing technologies, increasing sodium salt dissociation and lowering the sodium ion migration barrier are generally considered to be inherently contradictory. This is because enhancing dissociation requires strengthening coordination interactions, which often increases migration resistance; conversely, weakening coordination, while reducing migration resistance, is detrimental to salt dissociation. Therefore, those skilled in the art generally believe that it is impossible to simultaneously achieve high sodium salt dissociation and low migration barrier in the same polymer electrolyte. Those skilled in the art typically choose one direction for optimization rather than attempting to combine both.

[0027] This invention constructs a polymer system by simultaneously introducing Lewis base sites and Hammett-type strong electron-withdrawing substituents into the polymer system. The Lewis base sites and Hammett-type strong electron-withdrawing substituents synergistically regulate the process, thereby creating a polymer system that possesses both strong sodium salt dissociation capability and low Na+ content. + An all-solid-state polymer electrolyte with a migration barrier, in which the Lewis base site can interact with sodium ions, promoting sodium salt dissociation and increasing the migratory potential of Na+. + The concentration of sodium ions is controlled, ensuring continuous migration. Strong electron-withdrawing substituents can weaken the binding between sodium ions and binding sites through inductive effects and local dipole interactions, lowering the sodium ion migration energy barrier and accelerating ion migration kinetics. This achieves a synergistic improvement in ionic conductivity and electrode / electrolyte interface stability, significantly enhancing the fast-charging performance and ultra-long-cycle stability of sodium metal capacitors at high current densities.

[0028] Specifically, ionic conductivity is an important physical indicator characterizing the ion transport capacity in solid electrolytes. Higher ionic conductivity is generally beneficial for Na+. + Rapid migration in electrolytes.

[0029] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the polymer all-solid electrolyte is in the form of a membrane, that is, the polymer all-solid electrolyte is a polymer all-solid electrolyte membrane, and the thickness of the polymer all-solid electrolyte is 20-80 micrometers, for example, it can be 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, 45 micrometers, 50 micrometers, 55 micrometers, 60 micrometers, 65 micrometers, 70 micrometers, 75 micrometers or 80 micrometers.

[0030] In the aforementioned polymer all-solid-state electrolyte, as an optional embodiment, the mass ratio of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents to the polymer matrix is ​​(0.1-10):1, for example, 0.1:1, 1:1, 2:1, 3:1, 5:1, 7:1, 9:1, or 10:1, preferably (0.1-3):1. The role of the polymer matrix is ​​to ensure that the polymer all-solid-state electrolyte has good film-forming properties and good mechanical properties.

[0031] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the mass ratio of the polymer matrix to the sodium salt is 1:(0.2-5), for example, it can be 1:0.2, 1:0.4, 1:0.8, 1:1, 1:2, 1:3, 1:4 or 1:5.

[0032] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the fluoroalkyl group includes at least one of polyfluoroalkyl and perfluoroalkyl groups.

[0033] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is a random copolymer, and the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained by copolymerizing a first functional monomer containing Lewis base sites and a second functional monomer containing Hammett-type strong electron-withdrawing substituents.

[0034] Compared to block copolymers, this invention defines the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents as a random copolymer. Specifically, this functional polymer is obtained by random copolymerization of a first functional monomer containing Lewis base sites and a second functional monomer containing Hammett-type strong electron-withdrawing substituents. This allows the polymeric all-solid-state electrolyte containing this functional polymer to exhibit stronger sodium salt dissociation ability and lower Na+ content. + Migration barrier.

[0035] Specifically, block copolymers are copolymers formed by polymerizing two or more different monomers into long chain segments, and then connecting these long chain segments together through chemical bonds.

[0036] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the number average molecular weight of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is 10,000-80,000 g / mol, for example, it can be 10,000 g / mol, 20,000 g / mol, 30,000 g / mol, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 70,000 g / mol or 80,000 g / mol.

[0037] In the aforementioned polymer all-solid-state electrolyte, as an optional embodiment, the molar ratio of the first functional monomer containing a Lewis base site to the second functional monomer containing a Hammett-type strong electron-withdrawing substituent is 1:(0.4-10), for example, 1:0.4, 1:1, 1:3, 1:5, 1:7, 1:9, or 1:10. If there is too much second functional monomer, there will be too little first functional monomer, making it difficult to ensure sodium salt dissociation and provide continuous migration sites. If there is too little, it is insufficient for competitive regulation and insufficient to weaken the strong binding of sodium ions to coordination sites. This invention limits the molar ratio of the first functional monomer containing a Lewis base site to the second functional monomer containing a Hammett-type strong electron-withdrawing substituent to 1:(0.4-10), so that the weakly coordinating polar groups have a higher distribution density in the copolymer, thereby enhancing their binding to Na+. + The dipole regulation effect of the local coordination environment. At the same time, sufficient Lewis base sites are still retained in the system to promote sodium salt dissociation, thus enabling sodium salt dissociation and Na+ dissociation. + A better balance is achieved between migration and interface stability. This proportional design helps reduce Na... + Excessive coordination reduces migration resistance, thereby improving the ion transport capacity and electrode / electrolyte interface stability of all-solid-state polymer electrolytes.

[0038] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the first functional monomer containing Lewis base sites includes at least one of sulfobetaine monomers, carboxybetaine monomers, and phosphorylcholine monomers.

[0039] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the first functional monomer containing Lewis base sites includes at least one of sulfobetaine methacrylate (CAS No. 3637-26-1), carboxybetaine methacrylate (CAS No. 24249-95-4), and 2-methacryloyloxyethyl phosphocholine (CAS No. 67881-98-5).

[0040] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the second functional monomer containing a Hammett-type strong electron-withdrawing substituent includes at least one of 2,2,2-trifluoroethyl methacrylate (CAS No. 352-87-4), 2,2,2-trifluoroethyl methacrylate (CAS No. 407-47-6), 1,1,1,3,3,3-hexafluoroisopropyl methacrylate (CAS No. 3063-94-3), dodecafluoroheptyl methacrylate (CAS No. 2261-99-6), perfluorohexylethyl methacrylate (CAS No. 2144-53-8), 4-trifluoromethylstyrene (CAS No. 402-50-6), pentafluorostyrene, and nitrostyrene.

[0041] In the aforementioned all-solid-state polymer electrolyte, as an optional embodiment, the raw materials for preparing the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents include the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, a chain transfer agent, an initiator, and an oxygen scavenger. Adding an oxygen scavenger can improve the stability, conversion rate, and controllability of the free radical polymerization reaction, thereby facilitating the acquisition of functional polymers with more uniform composition and more controllable structure.

[0042] In the above-mentioned polymer all-solid-state electrolyte, as an optional embodiment, the chain transfer agent includes at least one of 4-cyano-4-(phenylcarbonylthio)pentanoic acid (CAS No.: 201611-92-9), 2-cyano-2-propyldodecyl trithiocarbonate (CAS No.: 870196-83-1), cumyl dithiobenzoate (CAS No.: 201611-77-0), and 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid (CAS No.: 870196-80-8).

[0043] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, and ammonium persulfate.

[0044] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the oxygen scavenger includes at least one of sodium dithionite, sodium sulfite, sodium bisulfite, ascorbic acid, glucose, and triethanolamine.

[0045] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the mass ratio of the chain transfer agent to the first functional monomer containing the Lewis base site is (0.005-0.5):1, for example, it can be 0.005:1, 0.01:1, 0.03:1, 0.05:1, 0.07:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1 or 0.5:1.

[0046] In the aforementioned polymer all-solid-state electrolyte, as an optional embodiment, the mass ratio of the initiator to the chain transfer agent is 1:(1-35), for example, 1:1, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, or 1:35. A too-large initiator / chain transfer agent ratio will result in faster polymerization but more dead chains, wider dispersion, and poorer end-group retention; a too-small initiator / chain transfer agent ratio will result in slower polymerization, lower conversion rate, and failure to achieve the target molecular weight.

[0047] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the mass ratio of the oxygen scavenger to the first functional monomer containing the Lewis base site is (0.0003-0.1):1, for example, it can be 0.0003:1, 0.0005:1, 0.001:1, 0.003:1, 0.005:1, 0.007:1, 0.009:1, 0.01:1, 0.03:1, 0.05:1, 0.07:1, 0.09:1, or 0.1:1. Insufficient oxygen scavenger can lead to low monomer conversion, long induction period, and fluctuations in polymer molecular weight and molecular weight distribution, resulting in decreased polymer solution viscosity, film uniformity, mechanical properties, and ion transport performance. Excessive oxygen scavenger may interfere with RAFT polymerization equilibrium and cause side reactions with chain transfer agents or polymer end groups. At the same time, residual oxygen scavenger and its reaction byproducts may change the ionic strength and chemical environment of the reaction system, thereby affecting the purity, film-forming properties, mechanical stability, ionic conductivity, and electrochemical stability of the resulting polymer.

[0048] In the above-mentioned polymer all-solid-state electrolyte, as an optional embodiment, the preparation method of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents includes the following steps: S1. Add the co-solvent to the first organic solvent and stir until it is uniformly dissolved to obtain a first organic solvent system containing the co-solvent; then add the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, the chain transfer agent, the initiator and the oxygen scavenger to the first organic solvent system containing the co-solvent, stir to remove oxygen under an inert atmosphere, and then carry out a polymerization reaction. After the reaction is completed, a reaction solution of a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained. S2. The reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 is added to the precipitant, stirred, and the polymer is precipitated. Then, solid-liquid separation is performed, and the obtained solid is dried to obtain the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents.

[0049] This invention prepares a functional polymer that combines sodium ion interaction sites and a localized electronic environment regulation unit by copolymerizing a first functional monomer containing a Lewis base site with a second functional monomer containing a Hammett-type strong electron-withdrawing substituent. When this functional polymer is combined with a polymer matrix and a sodium salt, it forms a uniform and stable fast-charging polymer all-solid-state electrolyte membrane, which helps improve ion transport efficiency and electrode / electrolyte interface stability at high current densities. Compared to liquid electrolytes, the electrolyte obtained by this invention reduces the risks of leakage, volatilization, and combustion. Compared to traditional single-coordination-regulated polymer electrolytes, this invention has comprehensive advantages in ion transport, interface stability, and device safety, and is suitable for sodium-based energy storage devices such as sodium metal capacitors.

[0050] This invention uses a small-molecule fluorinated monomer containing Hammett-type strong electron-withdrawing substituents, instead of a polymer containing Hammett-type strong electron-withdrawing substituents, as the second functional monomer. An oxygen scavenger is introduced during the polymerization process. This design improves the controllability of the copolymerization reaction, the uniformity of functional group distribution, and batch repeatability, allowing polar groups such as Hammett-type strong electron-withdrawing substituents to be more evenly distributed in the copolymer chain, thereby more effectively regulating Na... ⁺ Local coordination environment. The resulting functional polymer, as an organic functional regulating component, is dispersed in the polymer matrix, which helps to improve the ion transport capacity, film uniformity, and electrode / electrolyte interface stability of the all-solid-state polymer electrolyte, and is therefore more suitable for all-solid-state sodium metal capacitors.

[0051] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the first organic solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, and tetrahydrofuran.

[0052] In the aforementioned polymer all-solid-state electrolyte, as an optional embodiment, the co-solvent includes at least one selected from lithium chloride, lithium bromide, sodium chloride, sodium bromide, potassium chloride, and potassium bromide. The function of the co-solvent is to promote monomer dissolution.

[0053] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the mass-to-volume ratio of the first functional monomer containing the Lewis base site to the first organic solvent is 1 g:(5-100 mL), for example, it can be 1 g:5 mL, 1 g:10 mL, 1 g:15 mL, 1 g:20 mL, 1 g:25 mL, 1 g:30 mL, 1 g:35 mL, 1 g:40 mL, 1 g:50 mL, 1 g:60 mL, 1 g:70 mL, 1 g:80 mL, 1 g:90 mL or 1 g:100 mL.

[0054] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the mass ratio of the cosolvent to the first functional monomer containing the Lewis base site is (0.01-1):1, for example, it can be 0.01:1, 0.03:1, 0.05:1, 0.07:1, 0.09:1, 0.1:1, 0.3:1, 0.5:1, 0.7:1, 0.9:1 or 1:1.

[0055] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S1, the stirring temperature is 20-40°C (for example, it can be 20°C, 25°C, 30°C, 35°C or 40°C), and the time is 5-20 minutes (for example, it can be 5 minutes, 10 minutes, 15 minutes or 20 minutes).

[0056] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S1, the inert atmosphere includes a nitrogen atmosphere or an argon atmosphere.

[0057] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S1, the temperature of the stirring deoxygenation is 20-40℃ (for example, it can be 20℃, 25℃, 30℃, 35℃ or 40℃), and the time is 1-2h (for example, it can be 1.2h, 1.4h, 1.6h, 1.8h or 2h).

[0058] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S1, the polymerization reaction temperature is 60-80℃ (for example, it can be 60℃, 65℃, 70℃, 75℃ or 80℃), and the time is 2-24h (for example, it can be 2h, 4h, 6h, 10h, 15h, 20h or 24h).

[0059] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the stirring time in step S2 is 20-60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 50 min or 60 min.

[0060] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S2, the precipitant is a mixed solvent of alcohol solvent and alkane solvent; the alcohol solvent includes at least one of methanol, ethanol, isopropanol, and n-butanol; the alkane solvent includes at least one of n-hexane, cyclohexane, n-heptane, and petroleum ether; the volume ratio of the alcohol solvent to the alkane solvent is 1:(0.5-2), for example, it can be 1:0.5, 1:1, 1:1.5, or 1:2.

[0061] This invention, by limiting the precipitant to a mixture of alcohol and alkane solvents, can regulate the overall solvation capacity of the mixed system, ensuring sufficient precipitation of the target random copolymer while simultaneously washing away unreacted monomers, low-molecular-weight substances, and reaction residues as much as possible. When the proportion of alkane solvent is too low, the mixed solvent has a strong solvation capacity for the target functional polymer, leading to insufficient polymer precipitation and some polymer residue in the liquid phase, thus reducing product recovery. When the proportion of alkane solvent is too high, the solvation capacity of the mixed system decreases too rapidly, causing the polymer to aggregate quickly and form a dense precipitate, which is not conducive to the sufficient replacement and removal of residual solvent, inorganic salts, unreacted monomers, and low-molecular-weight byproducts. Therefore, controlling the volume ratio of alcohol solvent to alkane solvent within the range of 1:(0.5-2) is beneficial for balancing sufficient precipitation of the target polymer and impurity removal, improving polymer recovery and purification efficiency.

[0062] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S2, the drying temperature is 40-80℃ (for example, it can be 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 80℃), and the time is 12-24h (for example, it can be 12h, 14h, 16h, 18h, 20h, 22h or 24h).

[0063] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, in step S2, the volume ratio of the reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 to the precipitant is 1:(5-50) (for example, it can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45 or 1:50); the solid-liquid separation method includes vacuum filtration, filtration or centrifugation.

[0064] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate polymers, and polysiloxane polymers.

[0065] In the above-mentioned polymer all-solid electrolyte, as an optional embodiment, the sodium salt includes at least one of NaFSI (sodium bis(fluorosulfonyl)imide) and NaTFSI (sodium bis(trifluoromethylsulfonyl)imide).

[0066] In a second aspect, the present invention provides a method for preparing a polymer all-solid-state electrolyte as described in the first aspect, the method comprising the following steps: In an inert gas environment, the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, the polymer matrix, and the sodium salt are mixed, and the resulting mixture is dissolved in a second organic solvent and mixed evenly to obtain a mixed solution B; the mixed solution B is placed in a mold and then dried to obtain the polymer all-solid electrolyte.

[0067] In the above-mentioned method for preparing polymer all-solid electrolyte, as an optional embodiment, the second organic solvent includes at least one of ethylene glycol dimethyl ether, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, tetrahydrofuran, and 1,3-dioxolane.

[0068] In the above-mentioned method for preparing polymer all-solid electrolyte, as an optional embodiment, the mass-volume ratio of the polymer matrix to the second organic solvent is 1 g:(8-30 mL), for example, it can be 1 g:8 mL, 1 g:10 mL, 1 g:15 mL, 1 g:20 mL, 1 g:25 mL or 1 g:30 mL.

[0069] In the above-mentioned method for preparing polymer all-solid electrolyte, as an optional embodiment, the mixing temperature is 40-80℃ (e.g., 40℃, 50℃, 60℃, 70℃ or 80℃), and the time is 3-12h (e.g., 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or 12h).

[0070] In the above-mentioned method for preparing polymer all-solid electrolyte, as an optional embodiment, the mold includes a polytetrafluoroethylene mold.

[0071] In the above-mentioned method for preparing polymer all-solid electrolyte, as an optional embodiment, the drying temperature is 40-80℃ (e.g., 40℃, 50℃, 60℃, 70℃ or 80℃), and the time is 12-24 hours (e.g., 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours).

[0072] Thirdly, the present invention provides an application of a polymer all-solid-state electrolyte as described in the first aspect or a polymer all-solid-state electrolyte prepared by the preparation method described in the second aspect in a sodium-based solid-state energy storage device.

[0073] In the above applications, as an optional implementation, the sodium-based solid-state energy storage device includes at least one of sodium metal capacitors and sodium metal batteries.

[0074] The present invention will now be described in further detail with reference to specific embodiments and comparative examples.

[0075] Example 1 This embodiment provides a method for preparing a polymer all-solid-state electrolyte membrane, including the following steps: S1: Weigh 0.02g LiCl and add it to 10mL of dimethyl sulfoxide solvent. Stir at 20℃ for 5min to dissolve it evenly, obtaining a dimethyl sulfoxide solution containing the co-solvent LiCl. Then, add 2g sulfobetaine methacrylate (methacryloylethyl sulfobetaine), 0.6g 2,2,2-trifluoroethyl methacrylate (trifluoroethyl methacrylate), 0.01g 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]valeric acid (CAS No.: 870196-80-8), 0.01g azobisisobutyronitrile (CAS No.: 78-67-1), and 0.0006g... Sodium dithionite (CAS No.: 7775-14-6) was stirred at 20°C under a nitrogen atmosphere to remove oxygen for 1 hour, and then heated to 60°C for reversible addition-fragmentation chain transfer polymerization (RAFT) reaction. The mixture was stirred at low speed (350 rpm) for 2 hours to obtain a copolymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents (functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents).

[0076] S2: 10 mL of the reaction solution obtained in step S1 was added dropwise to a mixed solution of 33.3 mL of ethanol and 16.7 mL of n-hexane, and stirred for 20 min to precipitate a pale yellow solid. The solid was then filtered and dried at 40 °C for 12 h to obtain copolymer A (a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents) containing Lewis base sites and Hammett-type strong electron-withdrawing substituents. The number average molecular weight of copolymer A was 41338 g / mol.

[0077] S3: In an argon atmosphere glove box, 0.2g of copolymer A obtained in step S2, 2g of polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP (number average molecular weight of 130,000 g / mol) and 0.4g of sodium salt NaFSI (CAS No. 100669-96-3) were added to 16mL of ethylene glycol dimethyl ether and stirred at 40℃ for 3h to obtain a homogeneous mixed solution B; a portion of mixed solution B was transferred to a polytetrafluoroethylene mold and then placed in a vacuum oven at 40℃ for 12h to obtain a fast-charging polymer all-solid electrolyte membrane (polymer all-solid electrolyte) with a thickness of 50 micrometers.

[0078] Figure 6 This is the 1H NMR spectrum of copolymer A prepared in this embodiment. Figure 7 The infrared spectrum of copolymer A prepared in this embodiment is shown. Monomer 1 is 2,2,2-trifluoroethyl methacrylate, and monomer 2 is sulfobetaine methacrylate. Figure 6 and Figure 7 It can be seen that copolymer A was successfully synthesized.

[0079] Example 2 This embodiment provides a method for preparing a polymer all-solid-state electrolyte membrane, including the following steps: S1: Weigh 0.2g LiBr and add it to 20mL of N,N-dimethylformamide solvent. Stir at 30℃ for 15min to dissolve it uniformly, obtaining an N,N-dimethylformamide solution containing the co-solvent LiBr. Subsequently, add 0.4g carboxybetaine methacrylate, 1.23g methacrylate-1,1,1,3,3,3-hexafluoroisopropyl methacrylate, 0.02g 2-cyano-2-propyldodecyl trithiocarbonate (S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester) (CAS No. 870196-83-1), 0.0013g azobisisoheptanenitrile (CAS No. 4419-11-8), and 0.012g of [unspecified ingredient] to the N,N-dimethylformamide solution. Sodium sulfite was stirred at 30°C under a nitrogen atmosphere to remove oxygen for 1.5 h, and then heated to 70°C to carry out a reversible addition-fragmentation chain transfer polymerization (RAFT) reaction. The mixture was stirred at a low speed (350 rpm) for 10 h to obtain a reaction solution of a copolymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents (functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents).

[0080] S2: 20 mL of the reaction solution obtained in step S1 was added dropwise to a mixed solution of 200 mL isopropanol and 200 mL n-heptane, and stirred for 45 min to precipitate a pale yellow solid. The solid was then filtered, and dried at 60 °C for 20 h to obtain copolymer A (a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents) containing Lewis base sites and Hammett-type strong electron-withdrawing substituents. The number average molecular weight of copolymer A was 37,000 g / mol.

[0081] S3: In an argon atmosphere glove box, 6g of copolymer A obtained in step S2, 6g of polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP (number average molecular weight of 130,000 g / mol) and 4g of sodium salt NaFSI were added to 40mL of ethylene glycol dimethyl ether and stirred at 60℃ for 7h to obtain a homogeneous mixed solution B; a portion of mixed solution B was transferred to a polytetrafluoroethylene mold and then placed in a vacuum oven to dry at 60℃ for 18h to obtain a fast-charging polymer all-solid electrolyte membrane (polymer all-solid electrolyte) with a thickness of 50 micrometers.

[0082] Example 3 This embodiment provides a method for preparing a polymer all-solid-state electrolyte membrane, including the following steps: S1: Weigh 0.2g KCl and add it to 20mL of N,N-dimethylacetamide solvent. Stir at 40℃ for 20min to dissolve it uniformly, obtaining an N,N-dimethylacetamide solution containing the co-solvent KCl. Then, add 0.2g 2-methacryloyloxyethyl phosphorylcholine, 2.92g perfluorohexylethyl methacrylate (CAS No. 2144-53-8), 0.1g cumyl dithiobenzoate, 0.003g benzoyl peroxide, and 0.02g triethanolamine to the N,N-dimethylacetamide solution. Stir at 40℃ under an argon atmosphere to remove oxygen for 2h, then raise the temperature to 80℃ to carry out a reversible addition-fragmentation chain transfer polymerization (RAFT) reaction at a low speed (350). Stirring at rpm for 24 hours yields a reaction solution of a copolymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents (a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents).

[0083] S2: 20 mL of the reaction solution obtained in step S1 was added dropwise to a mixed solution of 166.7 mL methanol and 333.3 mL cyclohexane, and stirred for 60 min to precipitate a pale yellow solid. The solid was then centrifuged and dried at 80 °C for 24 h to obtain copolymer A (a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents) containing Lewis base sites and Hammett-type strong electron-withdrawing substituents. The number average molecular weight of copolymer A was 52000 g / mol.

[0084] S3: In an argon-atmospheric glove box, 8g of copolymer A obtained in step S2, 4g of polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP (number average molecular weight of 130,000 g / mol) and 4g of sodium salt NaFSI were added to 24ml of N,N-dimethylformamide and stirred at 80℃ for 10h to obtain a homogeneous mixed solution B; a portion of mixed solution B was transferred to a polytetrafluoroethylene mold and then placed in a vacuum oven to dry at 80℃ for 24h to obtain a fast-charging polymer all-solid electrolyte membrane (polymer all-solid electrolyte) with a thickness of 50 micrometers.

[0085] Comparative Example 1 The preparation method of the polymer all-solid electrolyte membrane provided in this comparative example is basically the same as that in Example 1, except that in step S1, "0.6g 2,2,2-trifluoroethyl methacrylate" is replaced with the same amount of sulfobetaine methacrylate.

[0086] Comparative Example 2 The preparation method of the polymer all-solid electrolyte membrane provided in this comparative example is basically the same as that in Example 1, except that in step S1, "2g sulfobetaine methacrylate" is replaced with the same amount of 2,2,2-trifluoroethyl methacrylate.

[0087] Comparative Example 3 The preparation method of the polymer all-solid electrolyte membrane provided in this comparative example is basically the same as that in Example 1, except that in step S1, 2g of sulfobetaine methacrylate is replaced with the same amount of ethyl methacrylate, and 0.6g of 2,2,2-trifluoroethyl methacrylate is replaced with the same amount of ethyl methacrylate.

[0088] Comparative Example 4 The preparation method of the polymer all-solid electrolyte membrane provided in this comparative example is basically the same as that in Example 1, except that in step S1, "0.6g 2,2,2-trifluoroethyl methacrylate" is replaced with the same amount of ethyl methacrylate.

[0089] Comparative Example 5 The preparation method of the polymer all-solid electrolyte membrane provided in this comparative example is basically the same as that in Example 1, except that sodium dithionite is not added in step S1.

[0090] Figure 8 This is a comparison of the gel permeation chromatography (GPC) curves of copolymer A prepared in Example 1 of this invention and copolymer A prepared in Comparative Example 5. Figure 8 As shown, the GPC curve of copolymer A obtained in Example 1 exhibits a narrower single-peak distribution with relatively concentrated peaks. In contrast, the GPC curve of copolymer A obtained in Comparative Example 5 is significantly broadened and shows a certain degree of asymmetry, indicating that its molecular weight distribution is wider. Combined with the dispersion coefficient obtained from the GPC test, it can be seen that the dispersion coefficient (1.2) of copolymer A obtained in Example 1 is lower than that of Comparative Example 5 (2.3), indicating that under the reaction conditions of this application, adding an appropriate amount of scavenger can improve the controllability of molecular weight growth during RAFT random copolymerization, thereby obtaining a random copolymer with a more concentrated molecular weight distribution.

[0091] Performance testing 1. Raman test Test Method: The polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples were tested using Raman spectroscopy to characterize the dissociation state of sodium salt in the electrolyte. During testing, the electrolyte membrane was cut and placed flat on the test stage, and Raman spectra were collected under an inert atmosphere or in a sealed environment. The Raman spectroscopy test range was 400–1800 cm⁻¹. -1 Preferred analysis of 700–800 cm -1FSI within range - The characteristic vibrational peaks of FSI. Through analysis of FSI... - Peak fitting of characteristic peaks yields free FSI. - and coordination FSI - The peak area was calculated, and the free FSI was calculated based on the peak area ratio. - and coordination FSI - The relative content of sodium salts is used to evaluate the degree of dissociation of sodium salts and Na. + -FSI - The strength of the interaction. Free FSI - Ratio = Free FSI - Peak area / (free FSI) - Peak area + coordination FSI - (peak area), the results are shown in Table 1 and Figure 1 As shown.

[0092] Table 1. Free FSI in polymer all-solid electrolyte membranes prepared in the examples and comparative examples. - relative content From Table 1, it can be seen at least that: (1) Comparing Example 1 with Comparative Example 4, it can be seen that the introduction of Hammett-type strong electron-withdrawing substituents into copolymer A significantly enhances the dissociation ability of sodium salt; (2) Comparing Example 1 with Comparative Examples 1-2, it can be seen that trifluoroethyl and sulfonate have a synergistic effect in terms of sodium salt dissociation ability.

[0093] Figure 1 Raman spectroscopy results for the polymer all-solid-state electrolyte membranes provided in Examples 1, 1, 3, and 4. Free FSI in Examples 1, 1, 3, and 4 is visible. - The proportions were 70.24%, 62.78%, 35.54%, and 51.20%, respectively, indicating that the fast-charging polymer all-solid electrolyte synergistically regulated by Lewis base sites and Hammett-type strong electron-withdrawing substituents has stronger sodium salt dissociation ability and higher carrier concentration.

[0094] 2. Ionic conductivity test Ionic conductivity testing method: The ionic conductivity of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples was tested. The polymer all-solid-state electrolyte membrane was sandwiched between two stainless steel blocking electrodes to assemble a stainless steel / electrolyte membrane / stainless steel symmetrical cell, and electrochemical impedance spectroscopy was used for testing. The test frequency range was 0.1 Hz to 1 MHz, and the perturbation voltage was 5 to 10 mV. The bulk resistance R of the electrolyte membrane was determined based on the intersection of the high-frequency region of the impedance spectrum with the real axis, and the ionic conductivity σ was calculated according to the formula σ=L / (R×S), where L is the thickness of the electrolyte membrane and S is the effective contact area between the electrode and the electrolyte membrane.

[0095] Activation energy testing method: The activation energy of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples was tested. The ionic conductivity of the polymer all-solid-state electrolyte membranes at different temperatures was measured using variable-temperature electrochemical impedance spectroscopy. The electrolyte membrane was sandwiched between two stainless steel blocking electrodes to assemble a stainless steel / electrolyte membrane / stainless steel symmetrical cell. After being kept at a set temperature, impedance testing was performed, and the ionic conductivity at each temperature (30-80 degrees Celsius, with one point taken every 10 degrees Celsius) was calculated. The conductivity was then determined according to the Arrhenius equation σ=A⋅exp(-E). a / (RT)), where T represents temperature in K, and R represents the molar gas constant, which has a value of 8.314 J·mol⁻¹. -1 •K -1 A linear fit was performed with 1000 / T as the abscissa and lgσ as the ordinate, and the activation energy E for ion migration was calculated from the fitting slope. a The results are shown in Table 2.

[0096] Table 2 shows the ionic conductivity and activation energy of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples. Table 2 shows at least the following: (1) Comparing Example 1 with Comparative Example 4, it can be seen that the introduction of Hammett-type strong electron-withdrawing substituents into copolymer A significantly reduced the activation energy, indicating that the Na+ activation energy was reduced. + The migration barrier makes Na + Migration resistance is reduced; as shown in Table 1, by introducing Hammett-type strong electron-withdrawing substituents into copolymer A, a copolymer that possesses both strong sodium salt dissociation ability and low Na+ content is obtained. + Polymer solid electrolytes with migration energy barriers can be used to improve ionic conductivity.

[0097] (2) Comparing Example 1 with Comparative Examples 1-2, it can be seen that in reducing Na + In terms of migration energy barrier (ion migration activation energy) and improving ionic conductivity, trifluoroethyl and sulfonate have a synergistic effect.

[0098] 3. Coulomb efficiency test Sodium-copper coulombic efficiency testing method: The sodium-copper coulombic efficiency of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples was tested. The polymer all-solid-state electrolyte membrane was sandwiched between a sodium metal sheet and a copper foil to assemble a Na||Cu half-cell. After the cell was allowed to stand, a sodium deposition / stripping cycle test was performed in constant current mode. In each cycle, a certain areal capacity of sodium was first deposited on the copper foil surface at a set current density, and then the sodium was stripped off to a set cutoff voltage at the same current density. The deposition capacity and stripping capacity were recorded. After 100 cycles, the efficiency was calculated according to the formula CE=Q. strip / Q plate Calculate the coulomb efficiency by multiplying by 100%, where Q strip Q represents the sodium stripping capacity. plate This represents the sodium deposition capacity. The test results are as follows: Figure 2 As shown.

[0099] Figure 2 This is a comparison of the coulombic efficiencies of Na-Cu half-cells prepared using the polymer all-solid-state electrolyte membranes provided in Example 1, Comparative Example 1, and Comparative Example 2. Figure 2 It can be seen that the coulombic efficiency of Comparative Example 1 remained below 95% and exhibited significant fluctuations during the cycling process, while the coulombic efficiency of Comparative Example 2 decreased substantially after 13 cycles. In contrast, Example 1 achieved an average coulombic efficiency of 97.8% after 100 cycles.

[0100] 4. Ratio Performance Test Rate performance testing method: The rate performance of the polymer all-solid electrolyte membranes prepared in the examples and comparative examples was tested. An all-solid sodium metal capacitor was assembled from an activated carbon positive electrode, a polymer all-solid electrolyte membrane, and a sodium metal negative electrode. The test was conducted using a constant current charge-discharge method within a set voltage window. The rates were sequentially set at 0.1, 0.2, 0.5, 1, 2, 5, 8, 10, 12, 15, 18, 20, 25, and 30 A·g. -1 Charge-discharge cycles were performed at various current densities, and the discharge specific capacity at each current density was recorded. After the high current density test, the current density was restored to 1 A·g. -1 The discharge specific capacity after recovery was recorded to evaluate the device's capacity retention and rate performance under different current densities. The test results are as follows: Figure 3 As shown.

[0101] Figure 3 This is a comparison chart of the rate performance of the polymer all-solid-state electrolyte membranes provided in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. It can be seen that the sodium metal capacitor assembled with the fast-charging polymer all-solid-state electrolyte provided in Example 1 achieves a rate performance of 0.1 Ag. -1 up to 30 A g -1At the current density, they all exhibited significantly higher capacity than Comparative Examples 1, 2 and 3, demonstrating excellent rate performance.

[0102] 5. Critical Current Density Test Test Method: Critical current density tests were conducted on the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples. The polymer all-solid-state electrolyte membranes were sandwiched between two sodium metal sheets to assemble a Na||Na symmetric cell. After the cells were allowed to stand, a stepped sodium deposition / stripping test was performed in constant current mode. The current density was increased gradually from low to high, maintaining the same deposition / stripping surface capacity at each current density, and the corresponding voltage-time curves were recorded. The cell was considered to have reached a failure state when the cell voltage showed a significant sudden increase, continuous fluctuation, or short-circuit failure. The highest current density at which sodium deposition / stripping could be stably performed before failure was defined as the critical current density. The test results are shown in Table 3.

[0103] Table 3. Critical current density of polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples. Table 3 shows at least the following: (1) Comparing Example 1 with Comparative Example 4, it can be seen that the introduction of Hammett-type strong electron-withdrawing substituents into copolymer A significantly increased the critical current density, indicating that the introduction of Hammett-type strong electron-withdrawing substituents into copolymer A can improve the stability of the electrode / electrolyte interface of the device.

[0104] (2) Comparing Example 1 with Comparative Examples 1-2, it can be seen that trifluoroethyl and sulfonate have a synergistic effect on the stability of the electrode / electrolyte interface.

[0105] 6. Long-cycle performance testing Long-cycle performance tests were conducted on the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples. The polymer all-solid-state electrolyte membranes were sandwiched between sodium metal sheets and AC positive electrode sheets to assemble AC||Na batteries.

[0106] Cyclic charge-discharge tests were conducted at a constant current density of 2 A·g. -1 The device underwent 100,000 cycles within a voltage window of 2-3.8V. Capacitance retention and coulombic efficiency were recorded during the cycles to evaluate the device's stability during long-term charge-discharge processes. The test results are shown in Table 4. Figure 5 As shown.

[0107] Figure 5 The polymer all-solid-state electrolyte membranes prepared for Example 3, Comparative Example 1, and Comparative Example 2 were tested at 2 A·g -1 Long-cycle performance at current density. At 2 A g-1 At the given current density, the initial discharge specific capacity of Example 3 was approximately 40.6 mAh·g. -1 After 100,000 charge-discharge cycles, the capacity retention rate reached 71%, while exhibiting an excellent coulombic efficiency of up to 99.95%, indicating highly reversible and robust electrochemical behavior. In contrast, Comparative Example 1 retained only about 23% of its capacity after 20,000 cycles, while Comparative Example 2 experienced a sharp decline in coulombic efficiency and failed after about 5,000 cycles.

[0108] Table 4 shows the number of cycles when the capacity retention of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples is 80%. 7. Exchange current density test Test methods: The exchange current density of the polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples was tested. The polymer all-solid-state electrolyte membranes were sandwiched between two sodium metal sheets to assemble Na||Na symmetric cells. After the cells were allowed to stand, linear polarization tests were performed using an electrochemical workstation. The test voltage range was -10 to 10 mV to -50 to 50 mV near the open-circuit voltage, and the scan rate was 0.1 to 5 mV·s. -1 Based on the obtained current density-overpotential curves, a linear fit was performed on the low overpotential region to obtain the polarization resistance, and the exchange current density was calculated to evaluate the deposition / stripping reaction kinetics of the sodium metal / electrolyte interface. The test results are as follows: Figure 4 As shown in Table 5.

[0109] Table 5. Exchange current density of polymer all-solid-state electrolyte membranes prepared in the examples and comparative examples. Figure 4 The diagram shows the exchange current density of the polymer all-solid-state electrolyte membranes provided in Examples 3 and Comparative Examples 1-3. The exchange current densities of Examples 3, 1, 2, and 3 are 0.13 mA·cm⁻¹. -2 0.09 mA·cm -2 0.06mA·cm -2 0.02 mA·cm -2 .Depend on Figure 4 As shown in Table 5, the fast-charging polymer all-solid electrolyte provided in this embodiment of the invention improves the ion exchange rate at the interface and accelerates the ion transport kinetics at the interface.

[0110] In summary, the fast-charging polymer all-solid-state electrolyte prepared by this invention, synergistically regulated by Lewis base sites and Hammett-type strong electron-withdrawing substituents, promotes sodium salt dissociation and enhances the mobility of Na+ through Lewis base sites.+ The concentration of Na is regulated by Hammett-type strong electron-withdrawing substituents. + The localized action environment and reduction of Na + Migration resistance is reduced, thereby improving ion transport efficiency and uniformity. The fast-charging polymer all-solid-state electrolyte has high ionic conductivity, which can improve ion transport uniformity and electrode / electrolyte interface stability under high current density, reduce the risk of leakage, volatilization and combustion associated with liquid electrolytes, and help suppress side reactions and dendrite growth at the sodium metal anode interface. When used in sodium-based energy storage devices, especially all-solid-state sodium metal capacitors, it is beneficial to improve the rate performance, ultra-long cycle stability and safety of the devices.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer all-solid-state electrolyte, characterized in that, The polymer all-solid electrolyte comprises: a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, a polymer matrix, and a sodium salt, wherein the Lewis base sites include at least one of sulfonate, carboxylate, and phosphate, and the Hammett-type strong electron-withdrawing substituents include at least one of fluoroalkyl, perfluoroaryl, and nitro-substituted aryl.

2. The polymer all-solid-state electrolyte according to claim 1, characterized in that, The polymer all-solid electrolyte is in the form of a film, and the thickness of the polymer all-solid electrolyte is 20-80 micrometers; And / or, the mass ratio of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents to the polymer matrix is ​​(0.1-10):1; And / or, the mass ratio of the polymer matrix to the sodium salt is 1:(0.2-5). And / or, the fluoroalkyl group includes at least one of polyfluoroalkyl and perfluoroalkyl groups; And / or, the number-average molecular weight of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is 10,000-80,000 g / mol; And / or, the polymer matrix includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate polymers, and polysiloxane polymers; And / or, the sodium salt includes at least one of NaFSI and NaTFSI.

3. The polymer all-solid-state electrolyte according to claim 1, characterized in that, The functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is a random copolymer. The functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained by copolymerizing a first functional monomer containing Lewis base sites and a second functional monomer containing Hammett-type strong electron-withdrawing substituents.

4. The polymer all-solid-state electrolyte according to claim 3, characterized in that, The molar ratio of the first functional monomer containing a Lewis base site to the second functional monomer containing a Hammett-type strong electron-withdrawing substituent is 1:(0.4-10). And / or, the first functional monomer containing the Lewis base site includes at least one of sulfobetaine monomers, carboxybetaine monomers, and phosphorylcholine monomers; And / or, the first functional monomer containing the Lewis base site includes at least one of sulfobetaine methacrylate, carboxybetaine methacrylate, and 2-methacryloyloxyethyl phosphocholine; And / or, the second functional monomer containing a Hammett-type strong electron-withdrawing substituent includes at least one of 2,2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, dodecafluoroheptyl methacrylate, perfluorohexylethyl methacrylate, 4-trifluoromethylstyrene, pentafluorostyrene, and nitrostyrene.

5. The polymer all-solid-state electrolyte according to claim 3, characterized in that, The raw materials for preparing the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents include the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, a chain transfer agent, an initiator, and an oxygen scavenger; the chain transfer agent includes at least one of 4-cyano-4-(phenylcarbonylthio)pentanoic acid, 2-cyano-2-propyldodecyl trithiocarbonate, cumyl dithiobenzoate, and 4-cyano-4-[[(dodecylthio)thiocarbonyl]thio]pentanoic acid; the initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and peroxide... The oxygen scavenger comprises at least one of benzoyl persulfate and ammonium persulfate; the oxygen scavenger comprises at least one of sodium dithionite, sodium sulfite, sodium bisulfite, ascorbic acid, glucose, and triethanolamine; the mass ratio of the chain transfer agent to the first functional monomer containing the Lewis base site is (0.005-0.5):1; the mass ratio of the initiator to the chain transfer agent is 1:(1-35); the mass ratio of the oxygen scavenger to the first functional monomer containing the Lewis base site is (0.0003-0.1):

1.

6. The polymer all-solid-state electrolyte according to claim 5, characterized in that, The preparation method of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents includes the following steps: S1. Add the co-solvent to the first organic solvent and stir until it is uniformly dissolved to obtain a first organic solvent system containing the co-solvent; then add the first functional monomer containing Lewis base sites, the second functional monomer containing Hammett-type strong electron-withdrawing substituents, the chain transfer agent, the initiator and the oxygen scavenger to the first organic solvent system containing the co-solvent, stir to remove oxygen under an inert atmosphere, and then carry out a polymerization reaction. After the reaction is completed, a reaction solution of a functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents is obtained. S2. The reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 is added to the precipitant, stirred, and the polymer is precipitated. Then, solid-liquid separation is performed, and the obtained solid is dried to obtain the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents.

7. The polymer all-solid-state electrolyte according to claim 6, characterized in that, The first organic solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, and tetrahydrofuran; And / or, the co-solvent includes at least one of lithium chloride, lithium bromide, sodium chloride, sodium bromide, potassium chloride, and potassium bromide; And / or, the mass-to-volume ratio of the first functional monomer containing the Lewis base site to the first organic solvent is 1 g: (5-100 mL). And / or, the mass ratio of the cosolvent to the first functional monomer containing the Lewis base site is (0.01-1):1; And / or, in step S1, the stirring temperature is 20-40℃ and the time is 5-20 minutes; And / or, in step S1, the inert atmosphere includes a nitrogen atmosphere or an argon atmosphere; And / or, in step S1, the temperature for stirring and deoxygenation is 20-40℃, and the time is 1-2 hours; And / or, in step S1, the polymerization reaction is carried out at a temperature of 60-80°C for 2-24 hours; And / or, in step S2, the stirring time is 20-60 min; And / or, in step S2, the precipitant is a mixed solvent of alcohol solvent and alkane solvent; the alcohol solvent includes at least one of methanol, ethanol, isopropanol, and n-butanol; the alkane solvent includes at least one of n-hexane, cyclohexane, n-heptane, and petroleum ether; the volume ratio of the alcohol solvent to the alkane solvent is 1:(0.5-2). And / or, in step S2, the drying temperature is 40-80℃ and the time is 12-24h; And / or, in step S2, the volume ratio of the reaction solution of the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents obtained in step S1 to the precipitant is 1:(5-50); the solid-liquid separation method includes vacuum filtration, filtration or centrifugation.

8. A method for preparing a polymer all-solid-state electrolyte as described in any one of claims 1-7, characterized in that, The preparation method includes the following steps: In an inert gas environment, the functional polymer containing Lewis base sites and Hammett-type strong electron-withdrawing substituents, the polymer matrix, and the sodium salt are mixed, and the resulting mixture is dissolved in a second organic solvent and mixed evenly to obtain a mixed solution B; the mixed solution B is placed in a mold and then dried to obtain the polymer all-solid electrolyte.

9. The method for preparing the polymer all-solid-state electrolyte according to claim 8, characterized in that, The second organic solvent includes at least one of ethylene glycol dimethyl ether, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, tetrahydrofuran, and 1,3-dioxolane; And / or, the mass-to-volume ratio of the polymer matrix to the second organic solvent is 1 g: (8-30 mL). And / or, the mixing temperature is 40-80℃, and the time is 3-12h; And / or, the mold includes a polytetrafluoroethylene mold; And / or, the drying temperature is 40-80℃, and the time is 12-24 hours.

10. The application of a polymer all-solid-state electrolyte as described in any one of claims 1-7, or a polymer all-solid-state electrolyte prepared by the preparation method described in claim 8 or 9, in a sodium-based solid-state energy storage device.